On Transmitting Expressiveness in Belarusian-English Poetic Translation - Sakalova, Yuliya (Research in Language, 2014)
The present article deals with various lexical, grammatical, stylistic problems encountered by translators while transmitting aspects of expressiveness of the original text (on the example of Belarusian-English poetic translation). The focus of attention is on basic transformation types, which are illustrated by the original and colourful examples. The author of the article considers not only purely linguistic aspects of translation, but also relevant pragmatic adaptation.